To solve the quadratic equation \(4x^2 + 4x - 15 = 0\) using the quadratic formula, we need to apply the formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In the given equation, the coefficients are:
- \(a = 4\)
- \(b = 4\)
- \(c = -15\)
First, we calculate the discriminant \(b^2 - 4ac\):
\[ b^2 - 4ac = 4^2 - 4 \cdot 4 \cdot (-15) = 16 + 240 = 256 \]
Now, we plug in the values into the quadratic formula:
\[ x = \frac{-4 \pm \sqrt{256}}{2 \cdot 4} \]
\[ x = \frac{-4 \pm 16}{8} \]
Now we calculate the two possible solutions:
- For \(x = \frac{-4 + 16}{8}\):
\[ x = \frac{12}{8} = 1.5 \]
- For \(x = \frac{-4 - 16}{8}\):
\[ x = \frac{-20}{8} = -2.5 \]
Thus, the solutions to the equation \(4x^2 + 4x - 15 = 0\) are:
\[ x = 1.5 \quad \text{and} \quad x = -2.5 \]
So the correct response would be:
x=1.5, x=−2.5